Comparing Optimal Debulking Surgery Outcomes between Anemic and Non-Anemic Ovarian Cancer Patients at Dr. Hasan Sadikin General Hospital Bandung in 2022 – 2023 - Wenardy Dewanto; Ali Budi Harsono; Muhammad Alamsyah Aziz (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: Ovarian cancer remains one of the most lethal gynecological malignancies. Optimal debulking surgery is one of the treatment options of ovarian cancer. Anemia was commonly observed in ovarian cancer patients, yet its association with the outcome of optimal debulking surgery remains unclear. This study aims to evaluate the association between preoperative anemia and the outcome of optimal debulking surgery.Methods: A case-control analytical observational study was conducted on 87 ovarian cancer patients who had undergone optimal debulking surgery at Dr. Hasan Sadikin General Hospital in 2022-2023. Data were collected from medical records and was analyzed using Chi-square test.Results: The majority of ovarian cancer patients at Dr. Hasan Sadikin General Hospital in 2022–2023 presented with mild to moderate anemia, accounting for 37,78% and 33,33% of cases, respectively. Only 24,44% had normal hemoglobin levels, while 4,44% had severe anemia. Optimal debulking was achieved in 76,7% of cases. No significant association was found between preoperative anemia and optimal debulking outcomes (p = 0,601; OR 1,21, 95% CI: 0,68–2,16).Conclusion: Preoperative anemia was not associated with optimal debulking surgery outcomes.Perbandingan Keberhasilan Optimal Debulking Surgery antara Pasien Kanker Ovarium dengan Anemia dan Non-Anemia di RSUP Dr. Hasan Sadikin Bandung Tahun 2022 – 2023AbstrakTujuan: Kanker ovarium merupakan salah satu keganasan ginekologi dengan angka kematian tertinggi. Optimal debulking surgery merupakan salah satu terapi utama pada pasien kanker ovarium. Anemia sering ditemukan pada pasien kanker ovarium. Namun, hubungan anemia dan keberhasilan optimal debulking surgery belum jelas. Penelitian ini bertujuan untuk mengevaluasi hubungan anemia preoperatif dan keberhasilan optimal debulking surgery pada pasien kanker ovarium.Metode: Metode penelitian yang digunakan adalah studi observasional analitik dengan desain case control yang melibatkan pasien kanker ovarium yang menjalani optimal debulking surgery di RSUP Dr. Hasan Sadikin Bandung periode 2022 – 2023. Data diperoleh dari rekam medis dengan total 87 pasien yang memenuhi kriteria inklusi. Analisis hubungan anemia preoperatif dengan keberhasilan optimal debulking surgery dilakukan dengan uji Chi square. Hasil: Mayoritas pasien kanker ovarium di RSUP Dr. Hasan Sadikin tahun 2022 – 2023 mengalami anemia ringan (37,78%) dan sedang (33,3%). Hanya 24,4% pasien memiliki kadar hemoglobin normal dengan 4,44% pasien mengalami anemia berat. Optimal debulking surgery berhasil dicapai pada 76,6%. Tidak ditemukan hubungan bermakna antara anemia preoperatif dan keberhasilan optimal debulking surgery (p = 0,601; OR 1,21; 95% CI : 0,68-2,16)Kesimpulan: Hasil penelitian menunjukkan anemia preoperatif tidak berhubungan dengan keberhasilan optimal debulking surgery pada pasien kanker ovarium.Kata kunci: Anemia; kanker ovarium; optimal debulking surgery